Marcha de absorção de nutrientes e crescimento de mudas de caramboleira enxertada com a cultivar nota-10 - Freitas, Narima; Prado, Renato de Mello [UNESP]; Rozane, Danilo Eduardo [UNESP]; Torres, Mariana Hortense; Arouca, Marina Burani (Universidade Estadual de Londrina (UEL), 2011)
The nutritional state of star fruit seedlings must be adequate for a successful field implementation. The objective of the present work was to study the growth and uptake of macro e micronutrients curves by star fruit plants budded with Nota 10 cultivar in nutrient solution conditions. The experimental design was randomized complete blocks, with four replications and six treatments, which were consisted by the times of collects during the 150 days of the experiment (each 25 days). In each collection, the plant growth was evaluated by the division of the plants in root, stem and leaves in order to obtain the height, diameter of the stem, leave area and the dry matter. The accumulation of dry matter followed sigmoidal adjustment, while the uptake of nutrients followed quadratic adjustment, except Mg, P, and Cu that followed sigmoidal adjustment. The accumulation of nutrients by star fruit seedlings 'nota 10' followed the sequence: N<K<Ca<P<Mg<Fe<Mn<Zn<B<Cu, where the absorption of nutrients was bigger in leaves than the stem and roots, in exception of the P, Zn, Fe and Cu. The period of greatest demand for nutrients was between 90 and 150 days after transplanting.
Growth and uptake of nutrients curves in star fruit plants budded with nota 10 cultivar
Keywords: Star fruit; Mineral nutrition; Nutrient accumulation; nutritional exigency; Averrhoa carambola L.